XVI International Symposium on Marine Natural Products|XI European Conference on Marine Natural Products - Pedrosa, Rui (2020)
The International Symposium on Marine Natural Products (MaNaPro) happened for the first time in 1975 in the city of Aberdeen, Scotland, organized by Professor Ronald H [...].